Persepsi pelajar terhadap amalan pengajaran tilawah Al-Quran - Che Noh, Mohd Aderi; Ahmad Tarmizi, Rohani (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2009)
This article was written to identify student perception towards the teaching instructions in the reading part of Tilawah al-Quran which was one of the components in the Islamic Education Integration Curriculum for daily Secondary school. The total of 1651 standard two student from all over Malaysia were selected by stratified and cluster samplings. The student were asked to give respond towards 69 indicators which were related to teaching instructions in Tilawah al-Quran based on the four components which were starting of the teaching, expansion of the education, closing of the education and assisted tools. Responses in the questionnaire were using 5 units of the likert scale. Descriptive statistics which were frequency, percentage and mean were used to describe the findings. Results of this study showed that the teaching methode were in the average satus (min=3.338).The mean for the teaching instructions according to the component showed that starting of the teaching (mean=3.461), closing of the teaching (mean=3.271) and assisted tools (mean=2.709). The expansion of education was in the highest state (mean=3.670). In conclusion all teachers should always try to improve their teaching instructions in Tilawah al-Quran to be the most effective so that the student could master Tilawah al-Quran without difficulty.